(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Sacrococcygeal pilonidal sinus (SC-PSD) is an acquired condition usually seen in young adults especially males associated with high recurrence rate after surgery.Many conventional surgical procedures are described for its management with their merits and demerits.The present study aims to evaluate the efficacy and determine effects of the Limberg flap rotation and its feasibility to the patients, their compliance, and outcomes such as wound infection, post- operative pain relief, recurrence rates, and return to work. Methods: 25 consecutive patients underwent Limberg flap reconstruction between January 2021 to may 2022 and were evaluated for various parameters. Results: All patients successfully underwent surgery, with very minimal postoperative pain, average hospital stay for 5 days, returned to work after 2 weeks with 1 patient having seroma, 1 having flap edema, 1 developed wound infection and no recurrences so far. Conclusions: Limberg flap reconstruction after excision of sacrococcygeal pilonidal sinus is an effective and reliable technique, easily performed, with high patient satisfaction, associated with complete cure and low incidence of post-operative complications.